TRAINING AND ESTABLISHMENT OF CODE BULE SYSTEM (EMERGENCY MANAGEMENT) IN ISLAMIC BOARDING SCHOOL DARUL MA’RIFAT GONTOR KEDIRI - Christrijogo Sumartono Waloedjo; Belindo Wirabuana; Dedi Susila; Soni Sunarso Sulistiawan (Universitas Airlangga, 2023)
A heart attack is the sudden cessation of effective heart function in a healthy-looking individual. In general, worldwide morbidity and mortality associated with heart attacks are enormous. This shows the importance of Basic Life Support training for the layman considering the many incidents of cardiac arrest outside the hospital that need a lot of time to get the help of trained health workers The purpose of this social service is to increase knowledge and skills in the field of Basic Life Support, participants are able to practice handling code blue in accordance with the procedures and the flow of fast and precise and carry out Tri-Dharma Higher Education Faculty of Medicine Unair and RSUD Dr.Soetomo. Specific targets to be achieved are the formation of Code Blue System at Pondok Pesantren Putra and the formation of BLS Citizen Community in Kediri. The method used in community service is by In-house training supported by lecture, demonstration and practice methods. The targets of this activity are the students who include 38 students who are given Basic Life Support training for one day, then compared the level of knowledge and attitude before and after (pre post-test design). Different test results obtained p value = 0.352 this value is above 0.05 so that the difference test of attitude before and after training is not different meaningful. However, it does not mean that the training process can be considered unsuccessful in improving the attitude of all participants, because the average attitudes value is still high, more than 4. This is presumably still good attitude retention from Basic Life Support training which has been given in the same population a year ago (December 26, 2016).